2014
DOI: 10.1017/jfm.2014.405
|View full text |Cite
|
Sign up to set email alerts
|

Pressure fluctuations produced by forward steps immersed in a turbulent boundary layer

Abstract: Experiments have been performed on the disturbance of a high-Reynolds-number turbulent boundary layer by three forward steps with sizes close to 3.8, 15 and 60 % of the boundary layer thickness. Particular attention is focused on the impact of the steps on the fluctuating surface pressure field. Measurements were made from 5 boundary layer thicknesses upstream to 22 boundary layer thicknesses downstream of the step, a distance equivalent to over 600 step heights for the smallest step size. Flow speeds of 30 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 27 publications
8
20
0
Order By: Relevance
“…In the same way, authors demonstrated that w > 9 is requiered to comfort the two-dimensional behavior of the flow. It is well known that the h δ ratio and the Reynolds number have significant effects on the reattachment length and turbulent statistics [2], but although the Ffs turbulent flows have been studied in the past, no consensus about these dependencies has been clearly reported in the literature. The constriction ratio C R = S d S u (where S u and S d are respectively the test section upstream and downstream from the step corner) seems to also have a significant effect on the separated flow fields, as reported by Lanzerstorfer and Kuhlmann [18].…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, authors demonstrated that w > 9 is requiered to comfort the two-dimensional behavior of the flow. It is well known that the h δ ratio and the Reynolds number have significant effects on the reattachment length and turbulent statistics [2], but although the Ffs turbulent flows have been studied in the past, no consensus about these dependencies has been clearly reported in the literature. The constriction ratio C R = S d S u (where S u and S d are respectively the test section upstream and downstream from the step corner) seems to also have a significant effect on the separated flow fields, as reported by Lanzerstorfer and Kuhlmann [18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the surface of a ship may be mostly smooth except for discontinuities in the hull where plates are joined. Such steps may be acoustically loud and interest lies in the study of the effect of steps on acoustic characteristics of flow [ 11 ] and the design of efficient low-noise vehicles. The program was used to evaluate an experimental study using data collected in the Stability Wind Tunnel at Virginia Tech (Blacksburg, VA, USA) ( Figure 1 ).…”
Section: Evaluation Of Microphone Array Datamentioning
confidence: 99%
“…The wind tunnel allows for experiments with anechoic (free from echo) or semi-anechoic conditions. The data evaluated below are part of a study on pressure fluctuations produced by forward steps immersed in a turbulent boundary layer [ 11 ]. Figure 2 shows a schematic of the test section, test wall and anechoic chambers.…”
Section: Evaluation Of Microphone Array Datamentioning
confidence: 99%
“…Wall-pressure fluctuations play a key role in a variety of engineering applications, such as flow-induced panel flutter and structural vibration, aircraft cabin noise and hydroacoustics of underwater vehicles (Blake 1970). Many investigations of wall-pressure fluctuations beneath a turbulent boundary layer have been performed in the past several decades, including zero pressure gradient turbulent boundary layer (Bradshaw 1967; Willmarth 1975; Farabee & Casarella 1991); flat-plate turbulent boundary layers with adverse pressure gradient (Mabey 1972; Simpson, Ghodbane & McGrath 1987; Na & Moin 1998 a , b ; Abe 2017); and turbulent flows over a backward- or forward-facing step (Farabee & Casarella 1986; Ji & Wang 2012; Awasthi et al 2014; Doolan & Moreau 2016). Presently, for turbulent flow in a channel with streamwise periodic constrictions, we analyse the pressure fluctuations by relating these to the mean pressure in the separation bubble and the development of the mixing layer.…”
Section: Introductionmentioning
confidence: 99%